Diabetic peripheral neuropathy based on Schwann cell injury: mechanisms of cell death regulation and therapeutic perspectives - Wu, Lijiao; Wang, Xiang Jin; Luo, Xi; Zhang, Jingqi; Zhao, Xinyi; Chen, Qiu (Frontiers in Endocrinology, 2024)
Diabetic peripheral neuropathy (DPN) is a complication of diabetes mellitus that lacks specific treatment, its high prevalence and disabling neuropathic pain greatly affects patients' physical and mental health. Schwann cells (SCs) are the major glial cells of the peripheral nervous system, which play an important role in various inflammatory and metabolic neuropathies by providing nutritional support, wrapping axons and promoting repair and regeneration. Increasingly, high glucose (HG) has been found to promote the progression of DPN pathogenesis by targeting SCs death regulation, thus revealing the specific molecular process of programmed cell death (PCD) in which SCs are disrupted is an important link to gain insight into the pathogenesis of DPN. This paper is the first to review the recent progress of HG studies on apoptosis, autophagy, pyroptosis, ferroptosis and necroptosis pathways in SCs, and points out the crosstalk between various PCDs and the related therapeutic perspectives, with the aim of providing new perspectives for a deeper understanding of the mechanisms of DPN and the exploration of effective therapeutic targets.